PENGARUH KESEPIAN TERHADAP DEPRESI MAHASISWA SELAMA PANDEMI - Purnomo, Andreas Wisnu Adi; Loekmono, J.T. Lobby (LPPM STKIP PGRI Bandar Lampung, 2020)
The implementation of the pandemic status and restrictions on social interaction in various lines of human life (including education) have a negative impact on human mental health. A mental health disorder that usually arises due to a lack of social interaction is loneliness. If the loneliness experienced by individuals cannot be handled properly, it can trigger other disorders such as depression. The purpose of this study was to find out how big and significant the loneliness variable was on depression in students who were undergoing online learning. This research is an Expost Facto type, the population that is the subject of the research is Guidance and Counseling students at the University in Salatiga. The sampling technique used proportional stratified random sampling with a margin of error of 10% and the subjects were 53 individuals. The data analysis technique used simple linear regression with the help of the Statistics Program for Service Solution version 16.0 for Windows. Based on the results of the analysis that has been carried out, it is found that the R-value is 0.733 which means that the level of closeness of the relationship is in a strong category. While the R2 value is 0.537, which means that the lonely variable contributes to the depression variable by 53.7%. Then the significance coefficient value is 0.000 <0.05, which means that the lonely variable has a significant influence on depression experienced by students during the pandemic.